1986
DOI: 10.1111/j.1365-2125.1986.tb02821.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma concentrations and cardiac beta‐ adrenoceptor blockade‐a study with oral and intravenous bopindolol.

Abstract: 1 Bopindolol, an esterified P-adrenoceptor blocking drug, was administered to nine healthy male volunteers in oral (1 mg and 4 mg) and intravenous (1 mg) doses. Plasma concentrations determined using a radio-receptor assay (RRA) and high pressure liquid chromatography (h.p.l.c.) yielded almost identical results, indicating that hydrolysed bopindolol, the major metabolite, is responsible for the pharmacological activity of the drug. 2 After intravenous administration the half-life for the formation of the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This supports the hypothesis of a metabolic transformation of the parent compound into the active drug, hydrolysed bopindolol, in the body. In a pharmaco- kinetic study a relatively long invasion half life of the active compound was found (Aellig et al, 1985). In the same study it was found also that even after intravenous drug administration the maximum plasma concentration of the active metabolite is reached only about 2 h after the injection.…”
Section: Effects Of Daily Oral Doses Of I and 4 Mg Bopindolol For 5 Daysmentioning
confidence: 86%
See 1 more Smart Citation
“…This supports the hypothesis of a metabolic transformation of the parent compound into the active drug, hydrolysed bopindolol, in the body. In a pharmaco- kinetic study a relatively long invasion half life of the active compound was found (Aellig et al, 1985). In the same study it was found also that even after intravenous drug administration the maximum plasma concentration of the active metabolite is reached only about 2 h after the injection.…”
Section: Effects Of Daily Oral Doses Of I and 4 Mg Bopindolol For 5 Daysmentioning
confidence: 86%
“…This is Following oral administration the onset of action of equipotent B-adrenoceptor blocking doses of bopindolol is slower than that of pindolol or other ,-adrenoceptor blocking drugs. Furthermore, in studies in which the drug was administered intravenously (Aellig et al, 1985) despite the fact that a marked effect was observed within 30 min, the maximum effect was not attained until 3 h after injection. This supports the hypothesis of a metabolic transformation of the parent compound into the active drug, hydrolysed bopindolol, in the body.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous reports have indicated (1) the slowly reversible nature of binding of bopindolol to receptors [10]; (2) the presence of active metabolites [11]; (3) the shallow slope of the plasma concentration-effect relationship [12,13], and (4) the small dissociation Hosohata/Hattori/Shen/Okuyama/ Kaneko/Ohnuki/Suzuki/Nagatomo constant of the drug-receptor complex [14]. Our previous study [2] also showed a slow dissociation of bopindolol and metabolite 18-502 from ß-ARs in the rat and guinea pig heart using pharmacological methods and the radioligand-binding assay.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that bopindolol possesses long-acting ß-blocking action with high affinity and partial agonist activity to the ß-ARs in both healthy volunteers and animal models [9,11,13,14], suggesting that less frequent administration may be necessary than with most other ß-blockers [6,7,11]. It is well known that one active metabolite (18-502) also has strong ß-blocking action, suggesting that this metabolite also contributes to the long-lasting effects of bopindolol [2].…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been reported to explain the dissociating and/or residual inhibitory effects of bipindolol from ß-ARs in heart muscles; i.e. (1) the slowly reversible nature of binding of bopindolol from receptors [11]; (2) the presence of active metabolites [12]; (3) the shallow slope of the plasma concentration-effect relationship [13,14], and (4) small dissociation constant of the drug-receptor complex [15]. Our previous study [6] also showed slow dissociation of bopindolol and 18-502 from ß-ARs in the rat and guinea pig heart using pharmacological and the radioligand binding assay methods.…”
Section: Discussionmentioning
confidence: 99%